Predicting Financial Distress through Financial Ratios: The Mediating Effect of Profitability - Prayoga, Dimas; Herlinawati, Erna; Herlina, Listri (UMSurabaya Publishing, 2026)
This study examines the determinants of financial distress in construction companies during the period of escalating financial pressures from Q1 2021 to Q2 2025, focusing on the influence of the CR, DAR, and company size on financial distress, with ROA serving as an intervening variable representing profitability. A quantitative approach was applied using panel data from six construction firms publicly traded on the IDX, selected through purposive sampling. Panel data regression is used to test direct effects, and the Sobel method is applied to assess the mediating impact of ROA. The study results indicate that, individually, CR, DAR, and company size have an influence on ROA but are not significant. However, they collectively exhibit a significant impact when tested simultaneously. In the context of financial distress, the empirical results reveal that CR and company size positively and significantly impact financial distress. At the same time, DAR has a significant negative impact, and ROA also shows a positive and meaningful impact. Collectively, CR, DAR, company size, and ROA significantly affect the degree of financial distress. Such outcomes indicate that management must comprehensively monitor liquidity, leverage, firm size, and profitability to anticipate and minimize financial distress risks